Turkey’s Energy Strategic Planning in the Eastern Mediterranean: Business Planning – Challenges – Adjustments - Kanellopoulos, Anastasios Nikolaos; Galanis, Konstantinos (HAPSc Policy Briefs Series, 2022)
This paper attempts to describe Turkey’s energy strategy, through an approach of its strategic position, energy needs and policies. This analysis presents a modern approach to strategic analysis that concerns a country, as it uses models of international policy, business and energy analysis, which are mainly utilized in business sector of trade and energy. The combination of these models leads to a better and in-depth understanding of the Turkish political and economic reality, which determines the development and evolution of the Turkish energy strategy.